One-step molecular detection of the MYD88 L265P mutation by unlabeled probe genotyping analysis. Issue 1 (February 2015) - Poon, Kok-Siong; Liu, Te-Chih; Tan, Karen Mei-Ling; Koay, Evelyn Siew-Chuan
Abstract: The aim of our study was to establish an unlabeled probe genotyping approach for rapid detection of the MYD88 L265P mutation in the differential diagnosis of Waldenstrӧm macroglobulinemia patients. Analytical and clinical validation of the assay was performed using serially diluted amplicon-cloned standards, 14 clinical bone marrow aspirate samples, and 30 peripheral blood samples from healthy donors, respectively. The analytical validation results showed that the assay is able to reproducibly identify as low as 10% of the L265P mutant. Clinical validation results showed improved detection sensitivity for the L265P mutation compared to Sanger sequencing. With the simplicity, cost-effectiveness, specificity and rapidity, we foresee that the unlabeled probe HRM assay is a good alternative to substitute current established methods for routine diagnostic testing of the MYD88 L265P mutation.